Age and growth of the sand lobster Thenus orientalis (Lund) from Bombay waters - Kagwade, P V; Kabli, L M (Indian Journal of Fisheries, 2011)
Age of the sand lobster Thenus orientalis was determined by length frequency distributior. using scatter diagram technique. Growth rates of males and females were identical till the first 2 years after which the former recorded higher rate of growth. Males upto 3 and females upto 4.5 years contributed to the com:nercial trawl catches. Growth parameters estimated by the von Bertalanffy’s growth equation were: L = 368 mm, K = 0.1279 and T =- 0.7368 for males and L = 300 mm, K = 0.1690 and T = -0.7 for fem les. The growth pattern wa; retrogressive geometric throughout the life in this species.